Design, Mathematical Modeling, and Dynamic Optimization of a Speed Breaker-Based Vehicular Kinetic Energy Harvester - Pankaj Guria; Laxmikanta Bhuyan; Manoranjan Suna; Udaya Majhi; Sagar Kalaka; Tanushree Chaudhury (International Journal of Electrical Power and Machine Systems, 2026)
Decentralized energy harvesting methods are becoming more popular due to rapid urbanization and the rising need for sustainable infrastructure. The road-embedded vehicle kinetic energy harvester (VKEH) design, mathematical modelling, and experimental validation are presented in this work. This paper presents the structural engineering, continuum mathematical modeling, and experimental validation of an optimized road-embedded vehicular kinetic energy harvester (VKEH). The mechanism utilizes a spring- loaded, low-friction rack-and-pinion transmission coupled with a high-ratio compound gear train to convert transient downward vertical displacements into continuous high-velocity rotational mechanical energy for an electromagnetic DC generator. Dynamic mathematical formulations were derived using Newtonian mechanics to establish exact force-displacement relationships under dynamic wheel impact. Under a design vehicular axle load generating an impact force of 294.3 N across a controlled platform displacement of 0.05 m, the system harvests a gross linear mechanical energy input of 14.715 J per compression stroke. By implementing an optimized 1:22 step-up gearing configuration, the transient pinion speed is amplified to a steady-state generator shaft velocity of 1100 rpm, resulting in 0.409 W of continuous mechanical shaft power and a net rectified electrical power output of 0.327 W at 80% transducer efficiency. Parametric optimization assessments demonstrate that deploying the VKEH across an urban roadway with an average traffic flow of 500 vehicles/hour yields a continuous daily energy harvesting capacity of 16.35 Wh/day. This framework establishes a highly predictable, self-sustaining micro-generation paradigm suitable for powering off-grid roadside IoT infrastructure, CCTV monitors, and LED traffic signaling arrays.
Keywords: Compound Gearing Optimization; Kinematic Transmission; Kinetic Energy Harvesting; Micro-grid Infrastructure; Renewable Power Systems; Speed Breaker Mechanism